HbA1c is a risk factor for cardiovascular disease in association with oxidative stress in patients with type 2 diabetes mellitus - Palem, Siva Prasad (International Journal of Research in Medical Sciences, 2017)
Background: Cardiovascular disease (CVD) is a major cause of death in diabetic subjects. Glycaemic status is one of the vital factor involved in vascular complications. It was clear the effect of glycaemia on microvascular complications, but uncertain on macrovascular complications. As we know oxidative stress plays a major role in the development of atherosclerosis and cardiovascular disease. Since oxidative stress is a risk factor for cardiovascular disease, the study has designed to perceive an association between HbA1c and oxidative stress in patients with type 2 diabetes mellitus for early prediction of cardiovascular events. Methods: 120 subjects were taken into the study, among these 60 type 2 diabetic subjects and remaining 60 subjects were healthy controls. The parameters like HbA1c, MDA and FRAP were estimated by established methods. ‘Kruskal Wallis’ test was used for variables in the parameters and Pearson correlation test was used to perform correlation between HbA1c and oxidative stress. Results: High level of HbA1c and MDA, low level of FRAP were found in patients with type 2 diabetes than healthy controls. The study was also found HbA1c have positive association with malondialdehyde (MDA) and negative association with FRAP. Conclusions: HbA1c was positively associated with oxidative stress in patients with type 2 diabetes mellitus. In this scenario, type 2 diabetic patients with high level of HbA1c might have risk of cardiovascular events.